Online directory of libraries and information centers in Malaysia (ODLICM) / Huang Seow Ching - Huang, Seow Ching (2004)
Online Directory of Libraries and Information Centers in Malaysia (ODLICM) is a web-based system that can provide useful information on libraries and information in Malaysia. This site provides an interactive search capability, thus enhancing faster access to pertinent information. The system would provide information of libraries and information centers, for instance, the library's basic information and the director's information. Administrators of this site are able to add record to the database of this site. As most of the online directory of libraries and information centers sites encompass information for North American region, this ODLICM is a directory of libraries and information centers only in Malaysia. This report begins with the introduction part. The introduction part consists of the project definition, background to project, project overview, objective, scope, limitation, and project schedule. Next, literature review was discussed which comprises the role of literature review, approaches to literature review, and findings. Then, the methodology used to develop this system was described. The system analysis and design part consists of the system's functional and non-functional requirements, the system's architectural design, database design, program design, process design and the user interface design. The following part is the system implementation. The development environment, the program coding method and the database development was described. The system testing part followed next. It consists of unit testing, module testing and integration testing. Next is the system evaluation and conclusion. The system's strength and limitation are evaluated. Future enhancement is suggested and knowledge gained is stated. Problems encountered and the solutions are described rs well. Next is the questionnaire form and the survey results. Finally, the user manual describe to the users on how to use the system. In the analysis phase, a survey was conducted on 40 random samples in two towns to determine the requirements of the system. The findings of the survey indicate preference for an interactive system complemented with a search module. In Reviewing the tools to fulfill such requirements, Active Server Pages.Net (ASP.Net), Hypertext Markup Language (HTML), Java Scripting and VB Scripting are deemed most appropriate to program the system. ODLICM has five modules organized to login, add record, submit record, give feedback, and keyword search. With ODLICM, online searching are conducted in real time and the results are available almost immediately. Furthermore, this site is also an interactivity and easy to search and retrieval for information. Finally, online directory provides remote access, which means that the searcher and the files of documents do not have to be geographically adjacent.